PENGGUNAAN ANIMASI DENGAN MACROMEDIA FLASH UNTUK MENINGKATKAN DAYA INGAT TERHADAP MATEMATIKA PADA MATERI GEOMETRI DI KELAS X SMA NEGERI 3 BANDA ACEH - Ruwaida Muhammad (Universitas Islam Negeri Ar-Raniry, 2012)
This research aims to improve students’ memory in learning geometry using Macromedia Flash Animation of grade X at SMA Negeri 3 Banda Aceh. It is classroom action research consisted of 2 cycles and using the worksheets. Geometry test was given after formative test and students’ responses questionnaire in learning. At the end of the research, it shows that (1) in first cycle that the average post-test score is 76.5 and at the second cycle is 80.1;(2) The Formative score test is 73.4; (3) students attitudes and responses towards learningmathematics by using Macromedia Flash are: (a) It was easy to memorize Mathematics instructional in first cycle is 80.77% and at the second cycle is 86, 15%, (b). Students could easily understand Mathematics instructional in first cycle is 65.38% and second cycle is 80.77% and (c) Students were active in group learning activities is 92.31% in first cycle and 100% in the second cycle.